2005
DOI: 10.1097/01.don.0000137645.87493.cd
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic Management of Dens Evaginatus of Maxillary Central Incisors: A Rare Case Report

Abstract: Dens evaginatus is a disturbance in tooth development that produces a tubercle of hard tissue on the surface of the tooth. While prophylactic pulp capping is recommended for vital teeth, teeth with necrotic pulps require endodontic therapy or extraction. This rare case of a 24-yr-old Indian male with affected maxillary central incisors demonstrates the clinical consequences of dens evaginatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…[14] Cases of bilateral occurrence[151617] and rare cases are reported in molars,[18] premolars,[19] and maxillary central incisors. [20] An Indian study reported a prevalence of 0.5% of surveyed teeth;[21] however, according to a Chinese study, DI was found in 517 permanent teeth from 67 Chinese individuals, which account for 5% of DI. These authors believe that the prevalence of DI may be related to ethnic origin.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Cases of bilateral occurrence[151617] and rare cases are reported in molars,[18] premolars,[19] and maxillary central incisors. [20] An Indian study reported a prevalence of 0.5% of surveyed teeth;[21] however, according to a Chinese study, DI was found in 517 permanent teeth from 67 Chinese individuals, which account for 5% of DI. These authors believe that the prevalence of DI may be related to ethnic origin.…”
Section: Discussionmentioning
confidence: 99%
“…It may be subject to pulpal exposure if the cusp is removed or fractured by occlusal movement. Some researchers point out that the talon cusp should be differentiated from DE according to the location, incidence, and clinical appearance of the abnormality (Vasudev and Goel, 2005). Other scholars suggest the talon cusp and DE are the same type of anomaly (Levitan and Himel, 2006 (Hill and Bellis, 1984).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, in the event that a tooth is affected, its homologous counterpart will need to be investigated. Rare cases are reported for molars [16], premolars [15], and maxillary central incisors [17]. The cause for the appearance of dens invaginatus is unclear, but some evidence suggests familial and hereditary components [18].…”
Section: Introductionmentioning
confidence: 99%